Viabilidade do processo de enfermagem no contexto hospitalar - Leite, José Eugênio Lopes (2011)
The Nursing Process (NP) is considered as the dynamics of the systemized and inter-related actions of human care. We believe that the nursing manager, as the representative of all the nursing care provided in the hospital setting, is an important agent for the implementation of institutional policies, such as the NP, in the service. However, there is little information in the literature about the NP in the perspective of the nurse manager. The objective of this study was to analyze the viability of the Nursing Process in the hospital context based on the attitudes of the nurse managers toward the Process. We conducted a descriptive-exploratory research study, of quantitative approach, with a population of 45 nurse managers that worked in the state hospitals located in Natal, RN and in the university hospitals of the UFRN. Two instruments were used for the collection of data: a nursing process questionnaire, constructed for use in this study, and the scale for the measurement of the attitudes titled Positions on the Nursing Process. The population is predominantly feminine (91,0%) and have relative nursing practice experience (Mean=17,6 years). However, they have little experience in management (Mean=8,6 years). They express little knowledge of the PE nursing terms and little experience with the Process. They have a positive atitude toward the NP (Mean = 110,9); are favorable to its developement in the service (86,7%); 48,9% indicated little possibility of institutionalization in the service and 37,8% indicated large possibility. The Spearman test for association between the variables of attitude about the NP and the possibility of its institutionalization demonstrated a weak negative association in the total individual scores of the attitudes (-,316) as in the 20 itens of the instrument, with coefficients varying from 0,014 to 0,464. Factorial analysis of the instrument identified three underlying factors to the attitudes of the managers in this study: relevance, operationalization and collaboration, with Cronbach Alpha coeficients of 0,955, 0,844 and 0,807, respectively, and 0,956 for the whole instrument, indicating that the scale and its factorial subscales have internal consistency. We conclude that there is a weak tendency for the managers with a favorable attitude to have a negative perception about the possibility of institutionalization of the NP in the service. The favorable position does not appear to be sufficient for the viability of this methodology in the hospital sector, results that is worrisome for nursing. This situation suggests that the difficulties with the institution of the NP in the hospitals may be related to other factors, including the organizational conditions. We believe that the institucionalization of the NP in a servisse where it is not known and not practiced, constitutes the introduction of an innovative work technology that involves many demands, among them the adherence of the persons to the proposed innovation. This demands time and the institutional adjustments and the human resources necessary. In this process, the involvement of the health professional of the institution is necessary. This situation brings to light the discussions of professional autonomy, the action limits and perspectives, the redefinition of roles, delimiation (or consensus) of the objects of study and of the work processes, among others.